Oil and gas exploration in Seferihisar Uplift (Western Turkey) containing an operable-size gold deposit: Geochemical evidence for the presence of a working petroleum system - KARATAŞ, ATİLLA (SPRINGER HEIDELBERG, 2020)
In recent studies, the links between hydrocarbon accumulations and gold mineralizations have been examined. According to the results obtained from these studies, it has been reported that gold and hydrocarbons are carried and deposited by the same hydrothermal fluids. In the Seferihisar Uplift, the Efemcukuru Gold Operation possesses the largest proven gold reserves of Turkey. For this reason, in this study, it is aimed to investigate the oil and gas potential of the Seferihisar Uplift by conducting total petroleum hydrocarbons analyses on the samples taken from the natural cold-water resources. As a result of the analyses conducted, hydrocarbons have been detected in all the water samples. Organic geochemical methods have been used to determine the source of hydrocarbons detected in the water resources. The n-alkane hydrocarbons found in the water samples are the mature petroleum hydrocarbons, which are the geochemical evidence for a working petroleum system in the study area. Due to the presence of mature hydrocarbon-rich waters, the main structure in a maximum of 765 m depth determined in the study area according to gravity and magnetic data has a significant hydrocarbon potential to become an oil and/or gas reservoir.
Keywords: Reservoir-targeted oil and gas exploration; Total petroleum hydrocarbons (TPH) in water analysis; Hydrocarbon-rich water; Bornova flysch zone; Gold deposit; CARLIN-TYPE; MINERAL-DEPOSITS; SOUTHWESTERN GUIZHOU; WITWATERSRAND BASIN; ORGANIC-MATTER; MUD VOLCANISM; HYDROCARBON; GRAVITY; ORIGIN; ANOMALIES